Preparation and characterization of pectin-starch hydrogel modified with urea and lactic acid-based deep eutectic solvent for soil water retention / Amira Mohd Yusoff ... [et al.] - Mohd Yusoff, Amira; Md Raffe, Siti Noor Atiyah; Mohamad, Sarina; Yusof, Rizana (Penerbit UiTM (UiTM Press), 2025)
Hydrogels are 3D polymeric networks that can absorb and retain large amounts of water and benefit many industries, including agriculture. However, most hydrogels nowadays are synthetic, negatively affecting the environment and human health. In this study, two biodegradable hydrogels were prepared using natural polymers of pectin and starch with the addition of deep eutectic solvent (DES) of choline chloride: urea (ChCl: urea) and choline chloride: lactic acid (ChCl: LA) to increase the water absorption through the casting method. The hydrogel has been optimized using different concentrations of crosslinking agent and different concentrations of DES to obtain their highest water sorption. The properties of hydrogels, such as swelling ratio, water retention, mechanical strength, biodegradability, and seed germination, have been investigated using standard methods. The results showed that the optimized and pectin-starch-ChCl: urea, and pectin-starch-ChCl: LA successfully absorbed water up to 108.70% and 120.80% within one hour, respectively, compared to the control, pectinstarch hydrogel without DES (97.86%). The hydrogels were found to be biodegradable with a rate of degradation of 100% for pectin-starch-ChCl: urea and 95.75% for pectin-starch-ChCl: LA, which was better than the control of 90.25% after 20 days in soil. The germination seed testing showed that hydrogel with ChCl: LA significantly promoted the growth of bean seeds and could maintain soil moisture for 20 days.